Prevalence of burnout among German general practitioners: Comparison of physicians working in solo and group practices. - Annegret Dreher (PLoS ONE, 2019)
BACKGROUND:Studies from general practitioner (GP) populations from various European countries show a high prevalence of burnout, yet data from Germany are scarce and there are no data comparing GPs from solo versus group practices. METHODS:This cross-sectional survey addressed all GPs from a German network of family medicine practices comprising 185 practices. Participants were asked to fill in a self-administered questionnaire addressing socio-demographic and job-related characteristics. The German version of the Maslach Burnout Inventory was used to measure the dimensions emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA). Each participant was categorized as having high EE, high DP and low PA following pre-defined cut-offs. RESULTS:A total of 214 GPs from 129 practices participated: 65.9% male, 24.8% solo practice. Of all GPs, 34.1% (n = 73) scored high for EE, 29.0% (n = 62) high for DP, 21.5% (n = 46) low for PA and 7.5% (n = 16) for all three dimensions. A higher risk for EE was found among female physicians, those unsatisfied with their job, those using few stress-regulating measures regularly and those reporting bad work-life balance. Burnout prevalence was higher in GPs in group than in solo practices (37.9% vs. 28.8% had high EE, 33.1% vs. 18.9% had high DP and 22.8% vs. 18.9% had low PA). A significantly higher prevalence of burnout symptoms was found in group practice employees compared to group practice owners. CONCLUSION:Burnout prevalence was higher among physicians in group practices compared to solo practices. In group practices, employed, young, female and part-time working physicians showed a higher burnout risk.